Strategi Manajemen Kegiatan Ekstrakurikuler dalam Mengembangkan Potensi Akademik dan Non-Akademik Peserta Didik di Madrasah Ibtidaiyah - Ummatul Khoiriyah; A. Tohirin; M. Furqon Wahyudi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Education in Madrasah Ibtidaiyah demands an intact balance among intellectual, emotional, and spiritual intelligence. Extracurricular activities play a highly crucial role as a vehicle to develop students' academic and non-academic potentials holistically. However, empirical reality shows that its implementation in various madrasahs is often constrained by suboptimal management governance and the erroneous paradigm assuming these activities consume classroom study time. This qualitative research with a multi-site study design aims to describe and analyze in-depth the extracurricular management strategies at MIN I and MI ICP Nurul Ulum Bojonegoro. The main instrument in this research is the researcher themselves (human instrument). The data collection procedure utilized in-depth interviews, participant observation, and documentation study techniques. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing, both individually and cross-site. The research findings indicate that extracurricular management strategies have been implemented comprehensively through scientific talent mapping-based planning, professional coach organizing, integrative actuating, and quality-oriented controlling functions. The success of this management implementation is significantly supported by the transformational leadership of the madrasah principal and the synergy of the Three Education Centers (school, family, community) which effectively overcomes the constraints of limited time. Practically, this extracurricular management provides symbiotic implications in the form of a transfer of learning phenomenon, where honed character intelligence is proven to boost students' cognitive academic achievements. This research contributes to offering an integrative and adaptive extracurricular management model for the scientific development of Islamic basic education management.